PENGARUH MODEL PROBLEM BASED LEARNING DENGAN BANTUAN VIDEO YOUTUBE TERHADAP PENINGKATAN HASIL BELAJAR SISWA - Yova Marshanda Machaenas; Niny Makaliwe; Devyano V.F. Ranti (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
ABSTRACT The low learning outcomes of students and the predominance of teacher-centered instruction indicate the need for a learning model that can enhance student engagement in the learning process. This study aimed to analyze the effectiveness of the Problem-Based Learning (PBL) model assisted by YouTube videos on the learning outcomes of eighth-grade students at SMP Negeri 1 Touluaan. This study employed a quasi-experimental method using a non-equivalent control group design. The participants consisted of 50 students divided into an experimental class and a control class, with 25 students in each group. Data were collected through pretests, posttests, observations, and documentation and were analyzed using the N-Gain test and an independent samples t-test. The findings revealed that the learning outcomes of students who were taught using the Problem-Based Learning model assisted by YouTube videos were higher than those of students who received conventional instruction. Statistical analysis indicated a significant difference between the two groups, with a significance value of 0.038 (p < 0.05), and the improvement in learning outcomes was categorized as moderate based on the N-Gain score. These findings demonstrate that the implementation of Problem-Based Learning assisted by YouTube videos is effective in improving students' learning outcomes. In addition to enhancing students' understanding of the material, this model can serve as an alternative instructional strategy that promotes active participation, develops problem-solving skills, and optimizes the use of digital media in social studies learning at the junior high school level. ABSTRAK                                                        Rendahnya hasil belajar siswa dan masih dominannya pembelajaran yang berpusat pada guru menunjukkan perlunya penerapan model pembelajaran yang mampu meningkatkan keterlibatan siswa dalam proses belajar. Penelitian ini bertujuan untuk menganalisis efektivitas model Problem Based Learning (PBL) berbantuan video YouTube terhadap hasil belajar siswa kelas VIII SMP Negeri 1 Touluaan. Penelitian ini menggunakan metode eksperimen semu dengan desain non-equivalent control group. Subjek penelitian terdiri atas 50 siswa yang dibagi ke dalam kelas eksperimen dan kelas kontrol, masing-masing berjumlah 25 siswa. Pengumpulan data dilakukan melalui pretest, posttest, observasi, dan dokumentasi, kemudian dianalisis menggunakan uji N-Gain dan uji independent sample t-test. Hasil penelitian menunjukkan bahwa hasil belajar siswa pada kelas yang menerapkan model Problem Based Learning berbantuan video YouTube lebih tinggi dibandingkan dengan kelas yang menggunakan pembelajaran konvensional. Hasil uji statistik menunjukkan adanya perbedaan yang signifikan antara kedua kelompok dengan nilai signifikansi sebesar 0,038 (p<0,05) dan peningkatan hasil belajar berada pada kategori sedang berdasarkan nilai N-Gain. Temuan ini menunjukkan bahwa penerapan model Problem Based Learning berbantuan video YouTube efektif dalam meningkatkan hasil belajar siswa. Selain meningkatkan pemahaman materi, model ini dapat dijadikan alternatif strategi pembelajaran yang mendorong keaktifan siswa, mengembangkan kemampuan pemecahan masalah, serta mengoptimalkan pemanfaatan media digital dalam pembelajaran IPS di sekolah menengah pertama.